Efficient activation of persulfate by calcium sulfate whisker supported nanoscale zero-valent iron for methyl orange removal. Issue 1 (23rd December 2020) - Han, Yi; Zhou, Xian; Lei, Li; Sun, Huiqun; Niu, Zhiyuan; Zhou, Ziwei; Xu, Zhibing; Hou, Haobo
Abstract : In order to improve the utilization of nanoscale zero-valent iron (nZVI) in activating persulfate (PS), a composite material of nZVI/CSW with nZVI supported on calcium sulfate whiskers (CSWs) was synthesized in this study. Abstract : In order to improve the utilization of nanoscale zero-valent iron (nZVI) in activating persulfate (PS), a composite material of nZVI/CSW with nZVI supported on calcium sulfate whiskers (CSWs) was synthesized in this study. The activity of the nZVI/CSW-PS system was evaluated by the removal of methyl orange (MO) in the aqueous phase. With the optimization of response surface methodology (RSM), the degradation efficiency of 20.0 mg L −1 MO could increase to 98.13% in 5 min at the dosage of 1.03 g L −1 nZVI/CSW-2, 3.51 mM PS at a temperature of 40.8 °C. The results of scanning electron microscopy (SEM) and X-ray diffraction (XRD) tests showed that the nZVI particles were well dispersed on the CSW surface in a Fe 2+ /CSW molar ratio of 0.25 : 1, which is approximate to the theoretical value of 3.698 mg g −1 thin-layer-Fe supported on CSW. Furthermore, the results demonstrated that the thin-layer nZVI particles were the most efficient in activating PS, and nZVI was rapidly dispersed during the dissolution process of CSW, which greatly increased the reaction rate. γ-FeOOH is the main reaction product of nZVI/CSW-2. This study provides a novel advanced oxidation system with nZVI/CSW in wastewater pollution control.